The role of moral disengagement, anonymity perception, online disinhibition, and empathy in predicting cyberbullying perpetration among Chinese young adults - Abdullah, Haslinda; Kunhao, Zhang; Ma’rof, Aini Azeqa (Human Resource Management Academic Research Society, 2024)
This study investigates the influence of moral disengagement, anonymity perception, online disinhibition, and empathy on cyberbullying perpetration among Chinese young adults. A sample of 422 participants was analyzed using correlation and regression analyses to explore the relationships between these variables. The results indicate that moral disengagement and anonymity perception are strong predictors of cyberbullying perpetration, highlighting the tendency to rationalize harmful online behaviors when individuals feel detached from moral and social constraints. Online disinhibition also emerged as a key factor, showing that individuals who feel uninhibited in online spaces are more likely to engage in aggressive behavior. Conversely, empathy plays a protective role, with higher levels of empathy associated with lower engagement in cyberbullying. These findings suggest that reducing moral disengagement and anonymity, while fostering empathy, can help mitigate cyberbullying. Educational institutions and policymakers should implement programs that address these cognitive and emotional factors to promote safer online environments.